The effectiveness of additional long-term use of bottle-positive expiratory pressure in chronic obstructive pulmonary disease: A single-blind, randomized study. - KOCAKAYA, DERYA (My University, 2022)
Objectives: This study aimed to investigate the long-term use of bottle-positive expiratory pressure (PEP) in addition to breathing exercises as a home-based rehabilitation aid on exercise capacity, spirometric parameters, and quality of life in chronic obstructive pulmonary disease (COPD) patients. Patients and methods: From a total of 30 patients with stable moderate-to-severe COPD, 24 (22 males, 2 females; mean age: 62.4+7.2 years; range, 40 to 75 years) were included in the final study and randomized into two groups: the group that performed breath retaining techniques and the group that was instructed to use the bottle-PEP in addition to these techniques. Patients were evaluated with modified Medical Research Council scale, COPD assessment test (CAT), spirometry, St. George’s Respiratory Questionnaire (SGRQ), and 6-min walk distance (6MWD) before, three months and six months after the initiation of the program. Results: In the bottle-PEP group, patients’ mean 6MWD increased from 380.6±67.6 to 444.1±22.0 m (p=0.002), the mean CAT score decreased from 17.8±36.8 to 12.9±6.2 (p=0.03), and the mean SGRQ total score significantly decreased from 57.1±23.1 to 47.6±21.9 (p<0.05) after three months. The improvement in 6MWD continued in six months but disappeared in SGRQ and CAT scores. In the exercise group, only the 6MWD improved, and there were no significant improvements in other parameters regardless of time. There were no significant differences between the groups in any of the parameters at any follow-up session. Conclusion: While bottle-PEP does not significantly contribute when added to breathing exercises in patients with moderate-to-severe COPD in improving function and quality of life, it can be used as a safe choice in patients’ home rehabilitation programs.
Keywords: Chronic obstructive pulmonary disease; quality of life; randomized trial; rehabilitation; positive expiratory pressure